Agroecological practices and their influence on soil fertility in the coffee region of Xolotla, Puebla - Contreras Cruz, Andrea; Sánchez Morales, Primo; Romero Arenas, Omar; Rivera Tapia, José Antonio; Ocampo Fletes, Ignacio; Parraguirre Lezama, José Filomeno Conrado (Acta Universitaria, 2019)
Coffee (Coffea arabica L.) is a very important crop for the development of central and southern Mexico: 70% of the cultivated area is under traditional management. Due to the relevance of these agroecosystems, the objective was to identify agroecological practices (PA) and their influence on soil fertility in coffee systems in Xolotla, Puebla. To identify PA, a survey was applied to 79 producers. To determine the fertility of the soil, physicochemical analyzes were carried out based on the NOM-021-SEMARNAT; in addition, the total bacterial concentration was analyzed. It was found that 71% of the practices used in the management of coffee plantations are agro-ecological, and they have a positive relationship with the yield and nitrogen, potassium and calcium contents of the soil, as well as with the bacterial concentration of the soil. It is concluded that PA favor soil yield and fertility in the coffee agroforestry system.